2016 IEEE PES Innovative Smart Grid Technologies Conference Europe (ISGT-Europe) 2016
DOI: 10.1109/isgteurope.2016.7856276
|View full text |Cite
|
Sign up to set email alerts
|

Community power flow control for peak demand reduction and energy cost savings

Abstract: Abstract-The increase in penetration of renewable energy sources, such as solar or wind, and high peak load demand can cause grid network security issues. The incorporation of demand side management and energy storage devices can provide a solution to these problems. This paper presents a community power flow control (PFC) strategy which reduces peak grid demand, and increases self-consumption of renewable energy which produces energy cost savings in smart communities with grid-connected photovoltaic (PV) syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…This exercise shows that it is possible to preliminarily use GridLab-D in order to model a smart grid and show the benefits of its adoption. We note that our results obtained here are comparable with other studies (i.e., [13]- [14]), which individually look at the use of smart appliances and microgrids with solar capabilities. For example, in [13], a 25.4% reduction in energy use is reported when smart thermostats and appliances are used in residential homes.…”
Section: Simulation Results and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This exercise shows that it is possible to preliminarily use GridLab-D in order to model a smart grid and show the benefits of its adoption. We note that our results obtained here are comparable with other studies (i.e., [13]- [14]), which individually look at the use of smart appliances and microgrids with solar capabilities. For example, in [13], a 25.4% reduction in energy use is reported when smart thermostats and appliances are used in residential homes.…”
Section: Simulation Results and Discussionsupporting
confidence: 91%
“…For example, in [13], a 25.4% reduction in energy use is reported when smart thermostats and appliances are used in residential homes. In [14], using microgrid and smart grid technology for the reduction of peak loads, it is shown that an annual resuction of 32% in energy use could be achieved, where community power flow control strategies and consumption of self-generated renewable energy is utilized.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…DR programs utilize variable energy prices as an incentive for consumers to enforce the above-described methods. For this to be actually adopted by the consumers the divergence between peak and off-peak price has to be compelling [52].…”
Section: Demand Side Managementmentioning
confidence: 99%